How To Build A Shotgun Fruiting Chamber (SGFC) in 5 Easy Steps (FreshCap Mushrooms, 2017)
A SGFC, also known as a shotgun fruiting chamber, is one of the cheapest, easiest and quickest ways to get a suitable mushroom growing environment.